Perancangan perbaikan equipment kalibrasi pressure gauge dengan metode analisis perancangan kerja di PT. Surya Toto Indonesia Tbk - Junaedi Junaedi; Wanto Sarwoko; Riki Effendi (Universitas Muhammadiyah Metro, 2020)
In the calibration process of pressure gauge is very much needed accuracy, which can time consuming, especially in the inspection process and will affect the correction value of each inspection process. The work design application method is very useful for learning the principles and mechanisms for obtaining a better work system design or method. With using work design analysis then the work process is mapped into work maps. The aim of the research is to minimize working time by using work design application methods to determine the standard time and improvements that must be made by company. The results showed that the standard time for the pressure gauge calibration process before improvement was 3248.44 seconds. By using work design analysis, the time of the pressure gauge calibration process becomes more efficient with a standard time of 2291.86 seconds with an efficiency value of 91.72%.Keywords: Design, pressure gauge calibration equipment, work design method.